A Study on Perception of Financial Market Professionals in Turkey Towards Gold - OKUR, MUSTAFA (My University, 2021)
Gold becomes an important central bank reserve in Turkey, gold savings accounts and gold investment fundsbegun to increase with the increasing interest of the financial sector in last years. The risk appetite for gold isincreasing both in Turkish and international financial markets. The importance of gold as a financial instrumentis growing. Within this framework, the aim of this study is to analyze the perception of gold among theprofessionals in the Turkish financial market as a central bank reserve, a mean of payment and an investmentinstrument. The analysis was done by a survey made among the employees of the banks, broker firms andportfolio management companies in the Turkish financial sector, mainly among treasury departments, fund andportfolio managers. A perception score was calculated from the statistical data.

Türkiye’de geleneksel bir yatırım aracı olarak kabul gören altın son yıllarda önemli bir merkez bankası rezervi_x000D_ haline de gelmiş, finans sektörünün artan ilgisiyle altın tasarruf hesapları, altın yatırım fonları yaygınlaşmaya_x000D_ başlamıştır. Hem Türkiye’de hem de uluslararası piyasalarda altına yönelik yatırım iştahında artış görülmekte,_x000D_ finans sektöründe altının bir finansal enstrüman olarak önemi daha da artmaktadır. Bu çerçevede, bu çalışmanın_x000D_ amacı; Türk finans piyasasında çalışan profesyonellerin bir merkez bankası rezervi, ödeme ve yatırım aracı_x000D_ olarak altın algısını analiz etmektir. Analiz, Türk finans sektöründe yer alan; banka, aracı kurum ve portföy_x000D_ yönetim şirketi çalışanlarından, özellikle hazine/fon/portföy yöneticileri ve çalışanları arasında anket_x000D_ yöntemiyle yapılmış, elde edilen istatistiksel verilerden algı skoru hesaplanmıştır
Türkiye’de Finans Piyasası Profesyonellerinin Altına Yönelik Algısı Üzerine Bir Çalışma